William Walker papers - Walker, William, 1824-1860.
Fragments of letters, address, passport, and military script relating to Walker's career in Nicaragua during the Filibuster War.
U.S. born president of Nicaragua and adventurer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Nicaragua -- History -- Filibuster War, 1855-1860.; Nicaragua -- Politics and government -- 1838-1909.; Adventurers; Presidents -- Nicaragua